Consumers’ adoption of mobile payment: comparison between China and Malaysia / S-C Chuah …[et al.] - S-C, Chuah; S-T, Cao Stella; J-Y, Guo Trey; Z-J, Lian Ivey (Universiti Teknologi MARA, Shah Alam, 2019)
Mobile payment services has emerged as one of the prominent transaction payment methods. China is leading in mobile payment globally while mobile payment in Malaysia still in its infancy. This paper compares the factors in adoption of mobile payment among consumers’ in Zuhai, China and Kuala Lumpur, Malaysia. The factors included in the study were perceived usefulness, perceived ease of use, subjective norms and perceived security risk. A cross-sectional, descriptive study was undertaken on 96 smartphone users from China and 51 users from Malaysia. Inferential statistics Mann-Whitney U test was applied to compare between study variables. Spearman’s ho correlation was used to identify the association between the study variables and behavioral intention to adopt mobile payment services. The study found significant different between users’ perception on subjective norms and perceived security risk in these two city. There was no significant different for perceived usefulness and perceived ease of use between users in Zuhai and Kuala Lumpur. Significant negative linear correlations between perceived security risk and behavioral intention, and significant positive correlations between perceived usefulness, perceived ease of use and subjective norms and behavioral intention were observed from the study. The findings of this study indicate that the consumers in Kuala Lumpur have higher concern on mobile payment services security and greater social influences to adopt mobile payments.